Améliorer l’expérience des césariennes tout en réduisant leur taux. Perspectives transdisciplinaires sur l’introduction de la césarienne participative en Suisse romande - Caroline Chautems (Anthropologie & Santé, 2025)
In Switzerland, one in three births is by caesarean section. This rate contrasts with the criticisms levelled by public health organisations and some practitioners at obstetric interventionism as a cause of iatrogenic harm and detrimental to parents’ experiences. In response, Swiss hospitals have introduced “participatory” caesarean births to enhance parental agency, which is nevertheless restricted by institutional norms. Drawing on ethnographic research combining observations of prenatal consultations in two public hospitals and in-depth interviews with obstetricians, anesthetists (both physicians and nurses), and midwives, this article examines the implementation of “participatory” caesarean birth in French-speaking Swiss maternity hospitals and the transdisciplinary dialogue they have sparked. As part of the ongoing movement in favour of humanised childbirth, this new approach to cesarean births also highlights both the continuities and the limitations of this evolution.